Biocompósitos de liberação controlada/lenta de fertilizantes: avaliação em solo pela técnica Reflectometria no Domínio do Tempo - Medina, Ângela Fracon (Universidade Federal de São Carlos, 2018)
The use of fertilizer in agriculture is a widely used practice in the agricultural scenery. Over the years, the need to rise productivity in the growing areas will be inevitable in the face of population growth, reflecting the increased use of fertilizers and water. In this scenario, new technologies have emerged as a way of optimizing the amount of fertilizers used. One of the alternatives is the use of materials that release the nutrient in a controlled or slowly way, denominated fertireleasers. In this work, fertilizer materials based on a natural and biodegradable polymer, chitosan, were evaluated for their efficiency in the release of fertilizers in water and soil. The chitosan was used both with KNO3 fertilizer and montmorillonite clay, producing microspheres, microcapsules and macrospheres. The materials were inserted in the soil and the release of ions was analyzed by the Time Domain Reflectometry (TDR) technique. The measurements were made from probes inserted in containers containing sandy soil, with and without field capacity monitoring, getting results of humidity and electrical conductivity. The microcapsules present a slower release behavior in both water and soil, attributed to core-shell encapsulation. In spite of the rapid release in water (2h) the materials (QF2F, QAF2F, QRF2F, QRAF2F, QF3F, QAF3F, QRF3F e QRAF3F) presented continuous release in soil during the period of analysis (~100 days). Additionally, the release is dependent on water and since some materials retained water (QF3F, QAF3F), similar to hydrogels behavior. We concluded that the microspheres, microcapsules and macrospheres have different release in water and soil and this is characteristic of the composition of each material. It is worth noting that TDR, besides determining the ionic mobility in the soil, also allowed to evaluate other characteristics of the material such as the dependence of the release with the water, the hydrogel behavior, and the degradation of the material as a function of the lifespan.
Keywords: Liberação controlada; Fertilizante; Solo; Biocompósito; Controlled release; Fertilizer; Soil; Biocomposites; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO